Content Marketing Analysis in Marketing Communication Strategy using AIDA Theory in the Instagram application (Case Study of the Bumil_Pintar Instagram account) - Hafizhah, Izdihar Nisrina; Dewanti, Mentari Clara (East Asian Journal of Multidisciplinary Research, 2024)
Digital education for pregnant women not only provides necessary information, but also provides support, comfort and confidence as they prepare for the arrival of their little one. That way, this can also be felt by pregnant women whose gestational age is approaching birth and who are already vulnerable and cannot leave the house. Home Education Indonesia has several programs, and one of them is a webinar regarding education for pregnant women. Every day we also provide information about pregnant women via social media Instagram (@bumil_pintar). Research using descriptive qualitative methods, researchers try to analyze the content marketing phenomenon on the @bumil_pintar Instagram account in carrying out marketing communication strategies in the digital marketing era by using social media to educate and promote services offered to pregnant women. The interview and observation process was carried out on informants, namely 7 pregnant women who had attended the webinar on pregnant women. Home Education Indonesia has succeeded in implementing the AIDA theory (Attention, Interest, Desire, Action) in its promotional activities. In the aspect of attention, interesting and informative content is recognized as being able to attract the attention of potential webinar participants.